Diversifikasi Dan Karakterisasi Cita Rasa Bakso Ikan Kambing-Kambing (Abalisites Stellaris) Dengan Penambahan Bubur Wortel (Daucus Carota) Yang Berbeda - Sadawan Jumadi; Dwi Apriliani Ags; Amri Amin (Jurnal TILAPIA, 2021)
Abstract: Fish meatballs generally do not contain vitamin A and are less attractive in appearance. So to add and attract the appearance of fish balls, it is combined with carrot pulp. The aim was to determine the effect of adding 0gr, 5gr, 10gr, and 15gr carrot pulp. The materials used in this study were goat fish and carrot pulp. The research parameters were the organoleptic test of fish meatballs and the hedonic test (preference). The results of the study were added by adding 0gr, 10gr, and 15gr carrot pulp. The best organoleptic test results were goat fish meatballs with the addition of 10gr carrot pulp of 8.97 so that the meatballs were suitable for consumption. Furthermore, the best hedonic test results of goat fish meatballs with the addition of 10gr carrot pulp was 8.78 so that the meatballs were very, very popular.